Cyproterone acetate induces a wide spectrum of acute liver damage including corticosteroid‐responsive hepatitis: report of 22 cases. (16th July 2015) - Bessone, Fernando; Lucena, MI; Roma, Marcelo G.; Stephens, Camilla; Medina‐Cáliz, Inmaculada; Frider, Bernardo; Tsariktsian, Guillermo; Hernández, Nelia; Bruguera, Miquel; Gualano, Gisela; Fassio, Eduardo; Montero, Joaquín; et al.
Abstract: Background & Aims: Cyproterone acetate (CPA), an anti‐androgenic drug for prostate cancer, has been associated with drug‐induced liver injury (DILI). We aim to expand the knowledge on the spectrum of phenotypes and outcomes of CPA‐induced DILI. Methods: Twenty‐two males (70 ± 8 years; range 54–83) developing liver damage as a result of CPA therapy (dose: 150 ± 50 mg/day; range 50–200) were included. Severity index and causality by RUCAM were assessed. Results: From 1993 to 2013, 22 patients were retrieved. Latency was 163 ± 97 days. Most patients were symptomatic, showing hepatocellular injury (91%) and jaundice. Liver tests at onset were: ALT 18 ± 13 × ULN, ALP 0.7 ± 0.7 × ULN and total serum bilirubin 14 ± 10 mg/dl. International normalized ratio values higher than 1.5 were observed in 14 (66%) patients. Severity was mild in 1 case (4%), moderate in 7 (32%), severe in 11 (50%) and fatal in 3 (14%). Five patients developed ascitis, and four encephalopathy. One patient had a liver injury that resembled autoimmune hepatitis. Eleven (50%) were hospitalized. Nineteen patients recovered after CPA withdrawal, although three required steroid therapy (two of them had high ANA titres). Liver biopsy was performed in seven patients (two hepatocellular collapse, one submassive necrosis, two cholestatic hepatitis, one cirrhosis with iron overload and one autoimmune hepatitis). RUCAM category was 'highly probable' in 19 (86%), 'probable' in 1 (4%), and 'possible' in 2 (9%). Conclusions: CPA‐induced liver injury is severe and can be fatal, and may occasionally resemble autoimmune DILI. The benefit/risk ratio of this drug should be thoroughly assessed in each patient.